An infrared spectroscopic study of adsorbed species on nickel and platinum. - Moran, Lyle Edwin. (University of Ottawa (Canada), 1977)
In this thesis, infrared spectroscopy has been used to study adsorbed species on silica-supported nickel and platinum catalysts. The chemisorption of the oxides of nitrogen (particularly nitric oxide) was studied initially, followed by a study of the chemisorption and oxidation of pyridine on bare and oxidized nickel and platinum. The results of these studies will be described below. Infrared spectral data have shown that nitric oxide chemisorbs on Ni/SiO 2 to form a single adsorbed species, which has been attributed to linear, neutral Ni-NO. On Pt/SiO2 two major surface species were produced and these have been assigned to linear, neutral Pt-NO and bent Pt-NO. In addition, the spectral data have indicated that, at high surface coverage, other nitrogen-oxygen containing species are formed one of which has been tentatively identified as PtONO2. The study of nitrogen dioxide chemisorption has demonstrated that nitrogen dioxide dissociates on both Ni/SiO2 and Pt/SiO2 to form adsorbed nitric oxide and oxygen. Isotopic substitution experiments have shown that carbon monoxide and nitric oxide react over Ni/SiO2 to form a surface nickel isocyanate species and the formation of this species is independent of the order of the addition of the reactants. However, on Pt/SiO2 a surface isocyanate species was generated only if the nitric oxide was preadsorbed at low surface coverage. In both studies, it has been concluded that very little M-NCO is produced (M = Ni or Pt). When hydrogen was added to chemisorbed nitric oxide on Pt/SiO2, two new surfaces species are formed and these have been identified as Pt-NH 3 and Pt2O2NH. In addition to the above results, this thesis also contains extensive reviews of the chemisorption of nitric oxide and nitrogen dioxide and of the formation of surface isocyanate species on the transition metals. Pyridine. Infrared spectral data have indicated that pyridine dissociatively chemisorbs on Pt/SiO2 to form a Pt-C sigma bond at the 'ortho' position and a coordinate bond with the N-atom such that the molecule lies perpendicular to the surface. On Ni/SiO2 a different strongly adsorbed species is formed which has been identified as a simple nitrogen-coordinated pyridine which also lies perpendicular to the surface, and, as proposed by others, the coordination of this species is promoted if the nickel surface is pretreated with either CO or O2. When oxygen is added to chemisorbed pyridine on Pt/SiO2 two new adsorbed species are formed and these have been assigned to a surface (N=0) containing species of the type, PtNOx (x = 2 or 3) or Pt2NO, and a cyclic C5 derivative of unknown structure. The same species were formed on oxidized Pt/SiO2, but, in addition, coordinated pyridine is formed.
Keywords: Chemistry, Analytical.